From intra- to extra-uterine: early phase design of a transfer to extra-uterine life support through medical simulation - van Haren, J. S.; Delbressine, F. L. M.; Monincx, M.; Hoveling, T.; Meijer, N.; Bangaru, C.; Sterk, J.; van der Woude, D. A. A.; Oei, S. G.; van der Hout-van der Jagt, M. B. (Frontiers in Medical Technology, 2024)
Extra-uterine life support technology could provide a more physiologic alternative for the treatment of extremely premature infants, as it allows further fetal growth and development ex utero. Animal studies have been carried out which involved placing fetuses in a liquid-filled incubator, with oxygen supplied through an oxygenator connected to the umbilical vessels. Hence, by delaying lung exposure to air, further lung development and maturation can take place. This medical intervention requires adjustments to current obstetric procedures to maintain liquid-filled lungs through a socalled transfer procedure. Our objective was to develop obstetric device prototypes that allow clinicians to simulate this birth procedure to safely transfer the infant from the mother's uterus to an extra-uterine life support system. To facilitate a user-centered design, implementation of medical simulation during early phase design of the prototype development was used. First, the requirements for the procedure and devices were established, by reviewing the literature and through interviewing direct stakeholders. The initial transfer device prototypes were tested on maternal and fetal manikins in participatory simulations with clinicians. Through analysis of recordings of the simulations, the prototypes were evaluated on effectiveness, safety and usability with latent conditions being identified and improved. This medical simulation-based design process resulted in the development of a set of surgical prototypes and allowed for knowledge building on obstetric care in an extrauterine life support context.